ADVANCE YIELD TRIAL OF 10 RESISTANT RICE LINES TUNGRO DISEASE AT TUNGRO DISEASE RESEARCH STATION LANRANG SIDRAP - Elisurya Ibrahim; Fausiah T. Ladja; I Nyoman Widiarta (Agric, 2022)
One of the factors that influence national rice production instability is an attack of tungro disease that can lead to decreased production by up to 90% even if attacking in the vegetative period can cause crop failure. To reduce tungro disease in the field can be by using resistant varieties which are the most effective components in tungro control.Advanced yield trial is one step toprocess of producing tungro resistant varieties. This research aimed to identify the results of tungro resistant strains that have higher phenotypic character and yield potential than other tungro resistant varieties. The research was conducted at Tungro Disease Research Station, Lanrang Sidrap from December 2017 - March 2018 using a Randomized Complete Block Design (RCBD). were tentungro resistant lines and check varieties i.e Inpari 7 Lanrang and Ciherang and it was repeated 3 times. Data were analyzed using the F test and tested for significance with the Least Significant Difference (BNT). Correlation test was conducted between growth components, yield components and yields. The results showed that the lines tested had different >performances on the growth component, yield component and yield.There are three lines, namely BP12280-3f-7-Kn-2-1*B-Lrg-1-1-10-9, BP12206f-8-3-2*B-LR-20-4 and BP12280-3f-7-Kn-2-1*B-Lrg-1-16-14 which produced the highest productivity, which was supported by the number of filled grain per panicle and the number of panicles per clump.Flowering age 50%, number of panicles and number of filled grains were positively correlated with grain yield.